Spectrophotometric Determination of Trace Protein Using a New Inhibitive-Kinetic Indication Reaction System Protein-Tribromoarsenazo-Potassium Periodate - Yu, Hui; Hu, Wei-Hua; Zhou, Luo-Zeng; Zhai, Qing-Zhou (Asian Journal of Chemistry, 2011)
A novel kinetic spectrophotometric method for the determination of protein is proposed based on the inhibitive effect of bovine serum albumin (BSA) on the oxidation reaction of tribromoarsenazo (TBA) by potassium periodate (KIO4) in the medium of Clark-Lubs buffer solution in this study. The maximum absorption peak of the BSA-TBA-KIO4 system locates at 398 nm. The absorbance difference (DA) is linearly related to the concentration of bovine serum albumin over the range of 5-100 μg/mL and fitted the equation: DA = 0.0119 C (μg/mL) + 0.0737, with a correlation coefficient g = 0.9991. The detection limit of the method is 4.996 μg/ mL. The present method has been successfully used in the determination of the content of protein in soy milk and milk samples.